A comprehensive method of surface-line-point energy planning considering low-grade heat: A case study of an eco-agricultural park in Tianjin, China. (3rd April 2017) - Chen, Yan; Zhou, Mingyue; Deng, Na; Sheng, Ying; Zhang, Yufeng
Abstract : Buildings account for approximately 50% of the total energy consumption in the world. Efforts have been made to substitute low-grade thermal energy for fossil fuel to achieve thermal comfort in buildings in order to save energy and reduce air pollution. Generally, these efforts are either an incentive policy from the government or the specific technology on how to use one certain low-grade energy. However, the energy planning for a regional architectural complex or how to evaluate the applications of different forms of energy in advance is less published. For this reason, a comprehensive energy planning method for regional architecture complex using low-grade energy, named surface-line-point, is proposed in this article. The important indexes of the energy level gap and exergy price are adopted for surface planning. Exergy analysis can be used to realize the line planning. Hourly load simulation can be used to optimize the operation performance of machine and complete the point planning. The correctness and feasibility of this method is validated through a case study of eco-agricultural park in Tianjin. The surface-line-point planning can be further applied to other building groups to help the engineer select the most appropriate ways of energy supply.